Eksistensi Sanggar Gadih Lareh dalam Melestarikan Seni Tari Minangkabau pada Daerah Transmigrasi di Dharmasraya - Windi Novrianti; Indrayuda Indrayuda (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the existence of Sanggar Gadih Lareh in preserving Minangkabau Dance Art in the transmigration area in Dharmasraya. This research is a qualitative descriptive research. This research was carried out at the Gadih Lareh Studio located in Nagari Kurnia Koto Salak, Ke. Rumbai River, Dharmasraya Regency on June 3-09, 2024. Data obtained by data collection techniques (observation, interviews and documentation). The data was analyzed by qualitative descriptive analysis techniques. The results of this study show that: (1) The existence of dance in Sanggar Gadih Lareh is intended as a forum for the preservation of local wisdom in Dharmasraya, (2) The existence of Sanggar Gadih Lareh is the participation of every customary event, event and competition both inside and outside Dharmasraya Regency. Sanggar Gadih Lareh will display types of traditional dances, creations and dances created by Sanggar Seni Gadih Lareh.